Hawai'i's food consumption and supply sources: Benchmark estimates and measurement issues - Matthew K. Loke; PingSun Leung (Agricultural and Food Economics, 2013)
At the current time, Hawai?i lacks an established set of benchmark estimates on the availability of food for market consumption and its supply sources. This paper serves to fill a persistent gap in the existing literature by providing an estimation framework to map the existing food supply flows from various sources and to determine the various levels of food consumption in Hawai?i. The authors suggest modified measures of food self-sufficiency and import dependency to provide a more accurate assessment on the extent of food localization in Hawai?i. The analytical framework presented in this paper can be applied to other small, open (island or regional) economies with a food localization agenda, as it provides a more discrete and appropriate set of measurements, as well as offering the lessons gained through Hawai?i?s experience and challenges in the data-collating process. Local production and imports (continental United States and foreign countries) of consumable food in Hawai?i are estimated at just over 1.14 million tonnes in 2010. Food exports totaled 175.5 thousand tonnes, leaving total available food for consumption locally at 966.6 thousand tonnes. On a de facto basis, per capita food consumption in Hawai?i is estimated at 657.9 kilograms in 2010. At the food group level, fresh vegetables lead with per capita food consumption of 84.2 kilograms, followed by other proteins at 69.1 kilograms, fresh fruits at 67.7 kilograms, fresh milk at 62.9 kilograms, and rice at 27.9 kilograms. The analysis indicates that Hawai?i has an overall food self-sufficiency ratio (SSR) of 15.7% and an overall food import dependency ratio (IDR) of 102.5%. While it appears counterintuitive that the IDR exceeds 100%, this figure actually indicates the existence of food imports into Hawai?i that are then turned around and re-exported to other markets. With application of the more accurate localization ratio (LR), we estimate that only 11.6% of available food for consumption in Hawai?i was actually sourced from local production in 2010. Likewise, the modified import dependency ratio (MIDR) indicates that an estimated 88.4% of available food in Hawai?i was sourced from imports.
Keywords: 330; Food consumption; Supply sources; Benchmark estimates; Food self-sufficiency; Food localization; Import dependency